Civil procedure : rules, statutes, and other materials - Glannon, Joseph W.; Perlman, Andrew M. (Andrew Marcus); Raven-Hansen, Peter, 1946- (New York, NY : Wolters Kluwer Law & Business, 2011)
This resource is intended as a supplement to any civil procedure text to ensure that teaching materials are well rounded and up to date.
United States Constitution -- Federal rules of civil procedure -- Selected federal statutes -- Sample local rules -- Sample federal district judge standing order -- Selected federal rules of appellate procedure -- Selected federal rules of evidence.
Volumes for 2012- cataloged as a serial in LC.
Keywords: Civil procedure -- United States